Cognitive function enhancement in Alzheimer’s disease through traditional Chinese medicine rehabilitation nursing: meta-analysis - Zhao, Jinping; Dong, Xiaohong; Liu, Bin; Peng, Yubo; Yao, Zhuang (Frontiers in Psychiatry, 2025)
Alzheimer’s disease (AD) manifests as progressive cognitive deterioration with significant impact on patient independence and quality of life. While conventional treatments offer limited efficacy, Traditional Chinese Medicine (TCM) rehabilitation nursing presents a complementary approach deserving systematic evaluation. To synthesize existing evidence on the efficacy of TCM rehabilitation nursing for cognitive enhancement in AD through comprehensive meta-analysis. We conducted systematic searches across multiple electronic databases (PubMed, Embase, CNKI, Wanfang, and VIP) for controlled studies published from 2010 to present examining TCM rehabilitation nursing interventions for AD patients. Methodological quality was assessed using the Cochrane Risk of Bias 2.0 tool. Primary outcomes included Mini-Mental State Examination (MMSE), Activities of Daily Living (ADL), and treatment efficacy rates. Statistical synthesis employed RevMan 5.3 with random or fixed effects models based on heterogeneity assessment. Nine eligible studies encompassing 864 participants (432 intervention, 432 control) met inclusion criteria. Meta-analysis revealed significantly improved cognitive function in the TCM rehabilitation nursing group compared to conventional care, with MMSE scores showing substantial enhancement (mean difference = 4.63, 95% confidence interval: 3.74-5.53, P<0.00001). Treatment response analysis demonstrated higher rates of marked clinical improvement (risk ratio = 2.78, 95% CI: 1.65-4.70, P=0.0001) and substantially reduced treatment failure rates (85% reduction, P<0.00001). Though ADL scores showed positive trends, these did not reach statistical significance (P=0.07). TCM rehabilitation nursing demonstrates significant efficacy in enhancing cognitive function and treatment outcomes in AD patients. These findings support its integration into comprehensive care strategies, though additional research with standardized protocols is warranted for optimal implementation.